Representasi Kisah Pewayangan pada Iklan Sirup Marjan Versi “Baruna” dalam Perspektif Estetika Postmodern - Haryadi, Toto (Institut Seni Indonesia Yogyakarta, 2023)
The competition in advertising is so tight that causes over communication. Every company does different way, one of them is through creative advertising by highlighting the local culture which is rarely exposed by other companies. This has been done by the producer of Marjan syrup which is famous for presenting creative advertisements and received positive appreciation, especially the version of